Fezolinetant: A Promising New Non-hormonal Drug Against Menopausal Symptoms - Meducator, The; Nguyen, Anh; Chen, Lucy (The Meducator, 2025)
During menopause, up to 80% of individuals experience vasomotor symptoms, such as hot flashes, that severely impact quality of life. Fezolinetant is a novel oral drug that shows promise in treating hot flashes by acting as a neurokinin 3 receptor antagonist that restores hypothalamic thermoregulation. This review explores the effectiveness of Fezolinetant in reducing menopausal symptoms compared to the current pharmacological standard of care. We evaluate the strengths of Fezolinetant as an alternative treatment for patients that are eligible for traditional hormone replacement therapy and outline current limitations of the medication. The potential benefits of Fezolinetant warrant further research and post-market clinical trials to continue monitoring its efficacy and safety.